PENGARUH EARNING PER SHARE (EPS), DIVIDEND PER SHARE (DPS) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di BEI Periode 2016-2019) - Seny Tiara; Anik Malikah; Hariri Hariri (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this research is to find out how the effect of earnings per share (EPS), Dividend Per Share (DPS) and Return On Equity (ROE) on Stock Prices. In this study EPS, DPS and ROE are the independent variables while the stock price is the dependent variable. The data used in this study are secondary data. The population in this study are mining companies listed on the Indonesia Stock Exchange in the 2016-2019 period. Data collection techniques using purposive sampling. In this study using multiple regression analysis. The results of this study are simultaneously variable Earning per Share (EPS), Dividend per Share (DPS) and Return on Equity (ROE) simultaneously affect the Stock Price. And partially Earning per Share (EPS) has a significant positive effect on stock prices, Dividend per Share (DPS) has a positive effect on stock prices and Return on Equity (ROE) has a significant positive effect on Stock Prices.Keywords: Earning per Share (EPS), Dividend per Share (DPS) and Return on Equity (ROE) and Share Prices